FACTOR ANALYSIS OF FLY DENSITY LEVELS IN CHICKEN SLAUGHTERHOUSES - Juhemi; Fera Novitry; Berta Afriani (LPPM STIKES Al-Ma'arif Baturaja, 2025)
Fly density in chicken slaughterhouses is a critical issue as it affects environmental quality and public health. This study aims to analyze the factors influencing fly density levels, including temperature, humidity, lighting, and sanitation. A quantitative approach with a cross-sectional design was conducted at chicken slaughterhouses. Data were collected through observations and interviews using questionnaires and analyzed using chi-square tests to determine the relationships between variables. The results showed significant relationships between fly density and temperature, humidity, lighting, and sanitation, with p-values of 0.013, 0.000, 0.023, and 0.000, respectively. While most locations met the requirements for temperature, humidity, and sanitation, lighting conditions were still suboptimal. The study concludes that good environmental management, especially in lighting, ventilation, and waste management, is necessary to reduce fly populations. It is recommended that slaughterhouse managers improve ventilation, natural lighting, and waste management, while involving related stakeholders in sanitation education and environmental monitoring.